A Young Disabled LGBT+ Researchers Group: Working Collaboratively to Explore the Lives of Young Autistic LGBT+ Persons. (December 2022) - Toft, Alex; Ward, Beth; ,
This article explores setting up a research group and outlines how we work together. The goal of the research group is to work collaboratively to conduct research on aspects of life for young disabled LGBT+ people that we think need more research. We hope to outline the aim of the group and what we want to achieve. It will also discuss our research principles and how we have conducted research together. We hope that the article provides insight on how to set up collaborative groups, how to work together, and what such groups can achieve. This article has been written collaboratively and this is reflected throughout.